Business issues in management accounting (Hampshire : Workhouse Limited, 1995)
Offers a detailed explaination of Just in time (JIT) methods as a means of reducing waste from design to delivery. Lean manufacturing techniques, the Kaizen principle of continual improvement and the important role of management accountants in JIT are looked at in Hoover UK's white goods division and a Nissan manufacturing plant.
Copy available in DVD format
Title from data sheet
Keywords: Managerial accounting